The Special Tribunal for Lebanon law and practice - Alamuddin, Amal; Jurdi, Nidal Nabil; Tolbert, David (Oxford monographs in international humanitarian and criminal law, 2014)
This book looks at how the court was established, its foundational principles based on the Statute of the International Criminal Court and Lebanese domestic law, and the possible further development of its case law.